MENAKSIR NILAI INTEGRAL BESAR - Mutya Pratami; M. Natsir; Agusni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses a new method to estimate the value of the integral of the form Z M a exp(f (x))dx, where M → ∞ and x > 0. The discussion includes the reduction method with First Approximation and Further Approximations. Furthermore, supported by a few example of the use of this new method.